Intercultural education in a monocultural context: global and local dimensions of sensitive topics - Górak-Sosnowska, Katarzyna; Markowska-Manista, Urszula (Society Register, 2022)
The article critically engages in teaching intercultural education in Poland—a country that is to a great extent homogenous in ethnic or religious terms. It starts with a brief overview of the complicated nature of intercultural education, followed by a case study of how intercultural education is studied and researched in Poland in a top academic journal dedicated to intercultural education. Quantitative content analysis shows that intercultural education is generally approached and unrelated to the local Polish context. The only exception is the borderland type of intercultural education. This leads to a conclusion that teaching intercultural education without a context—i.e. real-life experiences—proves to be a challenge in monocultural schools.